Radioisotopic studies on equine infections anemia. II. Red cell mass and blood volume of thoroughbred horses determined with 51chromium - Maliska, Carmelindo (Pesquisa Agropecuaria Brasileira, 2014)
Red cell mass and blood volume of 16 Thoroughbred horses, 11 healthy and 5 with naturally acquired Equine lnfectious Anemia, were determined by means of  51Cr-tagged erythrocytes. The mean values obtained in healthy Thoroughbred horses were as follows:  red cell mass 40,64 and blood volume 102,32 ml/kg body weight. The mean red cell mass and blood volume in anemic horses were respectively 21,13 and 107,71 ml/kg body weight. The difference in the red cell mass values between the two groups was statistically significant (P < 0,01). There was significant correlation between erythrocyte mass and body weight (r = 0,89) in healthy horses.